On the Complexity of Finding Locally Optimal Solutions in Bilevel Linear Optimization - Prokopyev, Oleg A.; Ralphs, Ted K. (Operations Research, 2026)
On the Complexity of Finding Locally Optimal Solutions in Bilevel Linear Optimization